Effect of Different CH(3)NH(3)PbI(3) Morphologies on Photovoltaic Properties of Perovskite Solar Cells - Chen, Lung-Chien (Nanoscale Res Lett, 2018)
In this study, the perovskite layers were prepared by two-step wet process with different CH(3)NH(3)I (MAI) concentrations. The cell structure was glass/FTO/TiO(2)-mesoporous/CH(3)NH(3)PbI(3) (MAPbI(3))/spiro-OMeTAD/Ag. The MAPbI(3) perovskite films were prepared using high and low MAI concentrations in a two-step process. The perovskite films were optimized at different spin coating speed and different annealing temperatures to enhance the power conversion efficiency (PCE) of perovskite solar cells. The PCE of the resulting device based on the different perovskite morphologies was discussed. The PCE of the best cell was up to 17.42%, open circuit voltage of 0.97 V, short current density of 24.06 mA/cm(2), and fill factor of 0.747.